2014
DOI: 10.1152/ajprenal.00484.2013
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-bound fatty acids but not albumin itself alter redox balance in tubular epithelial cells and induce a peroxide-mediated redox-sensitive apoptosis

Abstract: Albuminuria is associated with metabolic syndrome and diabetes. It correlates with the progression of chronic kidney disease, particularly with tubular atrophy. The fatty acid load on albumin significantly increases in obesity, presenting a proinflammatory environment to the proximal tubules. However, little is known about changes in the redox milieu during fatty acid overload and how redox-sensitive mechanisms mediate cell death. Here, we show that albumin with fatty acid impurities or conjugated with palmita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…Several reports have shown that altered intra-renal FFA metabolism is associated with the pathogenesis of diabetic nephropathy [19,20,21,22,23,24]. Among these, decreased levels of lipolysis enzymes have been most extensively focused on as a therapeutic target for diabetic nephropathy [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that altered intra-renal FFA metabolism is associated with the pathogenesis of diabetic nephropathy [19,20,21,22,23,24]. Among these, decreased levels of lipolysis enzymes have been most extensively focused on as a therapeutic target for diabetic nephropathy [23].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence demonstrates that intra-renal lipid metabolism is altered in diabetic patients and animals, including enhanced lipogenesis and suppressed lipolysis, and that normalization of the alteration is essential for reducing FFA-mediated cytotoxicity [19,20,21,22,23]. These observations led us to hypothesize that the local alteration in FFA metabolism in diabetic PTECs impairs an adaptive response against the excess inflow of urinary SFA-bound albumin.…”
Section: Introductionmentioning
confidence: 99%
“…An inverse correlation exists between lipogenesis that is induced by the accumulation of fatty acids and the transcription of genes that are involved in fatty acid oxidation 22,23 . Fatty acids can also trigger apoptosis and, more importantly, create a toxic environment inside the cell that hinders mitochondrial function 24,25 . Fatty acid metabolism in disease states, such as AKI and diabetic nephropathy, will be discussed below.…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…High concentrations of albumin lead to PT apoptosis, though this response may be initiated by fatty acids bound to albumin rather than by albumin itself (101). Overnight exposure of human HKC-8 and porcine LLC-PK1 cells to high concentrations of albumin results in decreased expression of both Dab2 and Akt/PKB as well as megalin (95, 102), without alteration of fluid-phase endocytosis (103).…”
Section: Organization Of the Proximal Tubule Apical Endocytic Pathwaymentioning
confidence: 99%